1990
DOI: 10.1007/bf01974396
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear aberrations in hair follicle cells of patients receiving cyclophosphamide

Abstract: The toxic effect of cyclophosphamide on the proliferative cell population of hair follicles plucked from the human scalp was examined by the in vivo nuclear aberration assay. Patients participating in an independent clinical trial received oral low dose cyclophosphamide, intravenous high dose cyclophosphamide or oral placebo treatment. The percent of cells with nuclear aberrations (indicating apoptosis, a special form of cell death) and the percent of mitotic cells, in the hair matrix, were calculated for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Note that the current study was not designed to dissect which of the observed damage responses of organ-cultured human scalp HFs are specific to the agent tested and which ones reflect general follicular response pathways to chemical damage. We could reproduce the key parameters of CIA-induced hair damage that has been observed using pathological biopsies 6,9,30,31,71 as summarized in Table 1, which highlights and compares published CYP-induced effects on HFs in humans in vivo, in mice in vivo and in our in vitro model. Using a combination of morphological and molecular techniques, we demonstrate that these HFs respond to a key CYP metabolite (4-HC) in a manner that imitates chemotherapy-induced HF dystrophy and alopecia as it occurs in vivo: 4-HC induces melanin clumping and incontinence, down-regulates proliferation and massively up-regulates apoptosis of (predominantly) hair matrix keratinocytes, prematurely induces catagen, and up-regulates p53.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the current study was not designed to dissect which of the observed damage responses of organ-cultured human scalp HFs are specific to the agent tested and which ones reflect general follicular response pathways to chemical damage. We could reproduce the key parameters of CIA-induced hair damage that has been observed using pathological biopsies 6,9,30,31,71 as summarized in Table 1, which highlights and compares published CYP-induced effects on HFs in humans in vivo, in mice in vivo and in our in vitro model. Using a combination of morphological and molecular techniques, we demonstrate that these HFs respond to a key CYP metabolite (4-HC) in a manner that imitates chemotherapy-induced HF dystrophy and alopecia as it occurs in vivo: 4-HC induces melanin clumping and incontinence, down-regulates proliferation and massively up-regulates apoptosis of (predominantly) hair matrix keratinocytes, prematurely induces catagen, and up-regulates p53.…”
Section: Discussionmentioning
confidence: 99%
“…27,29 The clinical histopathology of CYP-induced alopecia was characterized several decades ago 4 -6,9,30,31 and has been reproduced in mice. 11,15,16 The key abnormalities of the human anagen HF in the so-called degeneration phase of CIA include atrophy of the hair matrix, tapering of the hair shaft, partial loss of inner and outer root sheath layers in vivo, shrinkage of the follicular dermal papilla (DP), premature apoptosis-driven 31 HF regression (catagen), and eventually, distortion of the entire HF architecture (severe HF dystrophy). The DP fibroblasts are much less affected, whereas massively and primarily affected cells are the keratinocytes of the hair matrix and the melanocytes of the HF pigmentary unit.…”
mentioning
confidence: 99%
“…EGF infusion induces apoptosis and thus catagen in sheep wool follicles (73). Apoptosis was described in the early stage of scarring alopecia (66) and in alopecia areata (83), and it is the standard response of the follicle to injury by irradiation or eytotoxie drugs (67)(68)(69). If one uses well-defined rodent models (e.g.…”
Section: Apoptosis In the Skinmentioning
confidence: 99%
“…Hyperptoliferative skin diseases like psoriasis, and hypoprolifetative disordets such as radiodertnatitis or the atrophy of ageing skin, are pritne targets for this strategy. Dermatologists have indeed long practised the thetapeutic tnanipulation of progratntned cell death without always realizing it: dithranol induced apoptosis (63,64), and several cytostatie drugs used in dertnatology as well as ionizing and UV-irradiation are prominent inducers of progratnmed cell death (68,69,77,80). Ideally, topical drugs are warranted that can specifically tnodulate the exeeution of keratinoeyte death programs in a localized fashion, for example by altering the expression of /)c7-2.…”
Section: Perspectivesmentioning
confidence: 99%
“…Several studies using animal models, in which alopecia was induced by drug treatment, suggested that alopecia induced by chemotherapeutics is principally mediated by the induction of apoptosis within the proliferative-epithelial compartment. 8,9 On the other hand, a study performed with morphological methods, indicated that apoptosis within the epithelial compartment is present in a low percentage of cells after treatment. 10 These preliminary statements lead us to further study the modality of cell death or degeneration that cooperates with apoptosis to drive HF degeneration.…”
mentioning
confidence: 99%